Long-Term Infusion of Acylated Ghrelin Blunts LH Surge and Diminishes the Superovulatory Response in Dairy Sheep - Ilias Ramouzis; Leda Oikonomopoulou; Ioannis Nanas; Konstantina Stamperna; Georgios S. Amiridis; Eleni Dovolou (Animals)
Ghrelin, the endogenous ligand of the growth hormone secretagogue receptor, is released pre-prandially and during periods of negative energy balance, exhibiting anti-fertility properties. In this study, twenty ewes were divided into two groups: a ghrelin-treated group receiving 1.25 μg/kg body weight (BW) of ghrelin per day via mini-pumps for 28 days and an untreated control group. Estrus was synchronized, superovulation was induced with FSH, and embryos and follicular fluid were collected six days post-estrus. Blood samples were taken to measure LH, progesterone, and anti-Müllerian hormone (AMH) concentrations. Results indicated that in treated animals, preovulatory LH surge was weaker, and progesterone levels were lower than in controls. Differences were observed in the superovulatory response and the number of collected embryos, both being higher in controls. While AMH levels did not differ between groups at the beginning of the experiment, they were lower in treated animals at the time of FSH administration. Treated ewes exhibited a reduced number of small follicles, and their follicular fluid contained lower AMH concentrations than the controls. These findings suggest that ghrelin plays a direct role in regulating LH secretion from the pituitary and in controlling ovarian follicle development, highlighting the strong interaction between nutrition and fertility.